In Vitro Digestibilities of Six Rumen Protected Fat-Protein Supplement Formulas - Hartati, Lilis; Agus, Ali; Widyobroto, BP; Yusiati, LM (ANIMAL PRODUCTION, 2012)
Abstract. The aim of the research was to evaluate the efficacy of protection method of rumen protected fat-protein supplements. In vitro digestibility test was carried out to examine nutrients digestibility of different supplement formula based on the sources of protein and oil. The research used two sources of fat namely crude palm oil (CPO) and fish oil (FO) and three sources of protein namely milk skim, soy flour, and soybean meal. Thus there were 6 combinations that subjected in the in vitro digestibility test. The observed variables were the digestibility of dry matter (DM), organic matter (OM), crude fat (CF), and crude protein (CP). Results indicated that the method for protecting protein and fat was effective. This was showed by low nutrients digestibility in the rumen and high nutrients digestibility in the post rumen. In conclusion the combination between skim milk and CPO gave the best results among the other supplement formula.Keywords: rumen protected nutrient, fat-protein supplement, rumen digestibility, in vitroAnimal Production 14(1):1-5, January 2012